Insights into genetics, human biology and disease gleaned from family based genomic studies. - Posey, Jennifer E; O'Donnell-Luria, Anne H; Chong, Jessica X; Harel, Tamar; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Buyske, Steven; Pehlivan, Davut; Carvalho, Claudia M B; Baxter, Samantha; Sobreira, Nara; Liu, Pengfei; et al. (Genet Med, 2019)
Identifying genes and variants contributing to rare disease phenotypes and Mendelian conditions informs biology and medicine, yet potential phenotypic consequences for variation of >75% of the ~20,000 annotated genes in the human genome are lacking. Technical advances to assess rare variation genome-wide, particularly exome sequencing (ES), enabled establishment in the United States of the National Institutes of Health (NIH)-supported Centers for Mendelian Genomics (CMGs) and have facilitated collaborative studies resulting in novel "disease gene" discoveries. Pedigree-based genomic studies and rare variant analyses in families with suspected Mendelian conditions have led to the elucidation of hundreds of novel disease genes and highlighted the impact of de novo mutational events, somatic variation underlying nononcologic traits, incompletely penetrant alleles, phenotypes with high locus heterogeneity, and multilocus pathogenic variation. Herein, we highlight CMG collaborative discoveries that have contributed to understanding both rare and common diseases and discuss opportunities for future discovery in single-locus Mendelian disorder genomics. Phenotypic annotation of all human genes; development of bioinformatic tools and analytic methods; exploration of non-Mendelian modes of inheritance including reduced penetrance, multilocus variation, and oligogenic inheritance; construction of allelic series at a locus; enhanced data sharing worldwide; and integration with clinical genomics are explored. Realizing the full contribution of rare disease research to functional annotation of the human genome, and further illuminating human biology and health, will lay the foundation for the Precision Medicine Initiative.
Keywords: Databases, Genetic; Genetic Diseases, Inborn; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; National Institutes of Health (U.S.); Pedigree; United States; Whole Exome Sequencing

WNT Signaling Perturbations Underlie the Genetic Heterogeneity of Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Coban-Akdemir, Zeynep; Bayram, Yavuz; Bahrambeigi, Vahid; Hoischen, Alexander; van Bon, Bregje W M; Gezdirici, Alper; Gulec, Elif Yilmaz; Ramond, Francis; Touraine, Renaud; Thevenon, Julien; et al. (Am J Hum Genet, 2018)
Locus heterogeneity characterizes a variety of skeletal dysplasias often due to interacting or overlapping signaling pathways. Robinow syndrome is a skeletal disorder historically refractory to molecular diagnosis, potentially stemming from substantial genetic heterogeneity. All current known pathogenic variants reside in genes within the noncanonical Wnt signaling pathway including ROR2, WNT5A, and more recently, DVL1 and DVL3. However, ∼70% of autosomal-dominant Robinow syndrome cases remain molecularly unsolved. To investigate this missing heritability, we recruited 21 families with at least one family member clinically diagnosed with Robinow or Robinow-like phenotypes and performed genetic and genomic studies. In total, four families with variants in FZD2 were identified as well as three individuals from two families with biallelic variants in NXN that co-segregate with the phenotype. Importantly, both FZD2 and NXN are relevant protein partners in the WNT5A interactome, supporting their role in skeletal development. In addition to confirming that clustered -1 frameshifting variants in DVL1 and DVL3 are the main contributors to dominant Robinow syndrome, we also found likely pathogenic variants in candidate genes GPC4 and RAC3, both linked to the Wnt signaling pathway. These data support an initial hypothesis that Robinow syndrome results from perturbation of the Wnt/PCP pathway, suggest specific relevant domains of the proteins involved, and reveal key contributors in this signaling cascade during human embryonic development. Contrary to the view that non-allelic genetic heterogeneity hampers gene discovery, this study demonstrates the utility of rare disease genomic studies to parse gene function in human developmental pathways.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Chromosome Segregation; Craniofacial Abnormalities; Diagnosis, Differential; Dwarfism; Female; Genes, Dominant; Genetic Association Studies; Genetic Heterogeneity; Humans; Limb Deformities, Congenital; Male; Middle Aged; Mutation, Missense; Phenotype; Urogenital Abnormalities; Wnt Signaling Pathway

Dual molecular diagnosis contributes to atypical Prader-Willi phenotype in monozygotic twins. - Jehee, Fernanda S; de Oliveira, Valdirene T; Gurgel-Giannetti, Juliana; Pietra, Rafaella X; Rubatino, Fernando V M; Carobin, Natália V; Vianna, Gabrielle S; de Freitas, Mariana L; Fernandes, Karla S; Ribeiro, Beatriz S V; Brüggenwirth, Hennie T; Ali-Amin, Roza; et al. (Am J Med Genet A, 2017)
We describe monozygotic twin girls with genetic variation at two separate loci resulting in a blended phenotype of Prader-Willi syndrome and Pitt-Hopkins syndrome. These girls were diagnosed in early infancy with Prader-Willi syndrome, but developed an atypical phenotype, with apparent intellectual deficiency and lack of obesity. Array-comparative genomic hybridization confirmed a de novo paternal deletion of the 15q11.2q13 region and exome sequencing identified a second mutational event in both girls, which was a novel variant c.145+1G>A affecting a TCF4 canonical splicing site inherited from the mosaic mother. RNA studies showed that the variant abolished the donor splicing site, which was accompanied by activation of an alternative non-canonical splicing-site which then predicts a premature stop codon in the following exon. Clinical re-evaluation of the twins indicated that both variants are likely contributing to the more severe phenotypic presentation. Our data show that atypical clinical presentations may actually be the expression of blended clinical phenotypes arising from independent pathogenic events at two loci.
Keywords: Adolescent; Base Sequence; Child; Chromosome Deletion; Chromosomes, Human, Pair 15; Comparative Genomic Hybridization; Exome; Facies; Female; Humans; Hyperventilation; Intellectual Disability; Obesity; Pathology, Molecular; Phenotype; Prader-Willi Syndrome; Transcription Factor 4; Twins, Monozygotic

REST Final-Exon-Truncating Mutations Cause Hereditary Gingival Fibromatosis. - Bayram, Yavuz; White, Janson J; Elcioglu, Nursel; Cho, Megan T; Zadeh, Neda; Gedikbasi, Asuman; Palanduz, Sukru; Ozturk, Sukru; Cefle, Kivanc; Kasapcopur, Ozgur; Coban Akdemir, Zeynep; Pehlivan, Davut; et al. (Am J Hum Genet, 2017)
Hereditary gingival fibromatosis (HGF) is the most common genetic form of gingival fibromatosis that develops as a slowly progressive, benign, localized or generalized enlargement of keratinized gingiva. HGF is a genetically heterogeneous disorder and can be transmitted either as an autosomal-dominant or autosomal-recessive trait or appear sporadically. To date, four loci (2p22.1, 2p23.3-p22.3, 5q13-q22, and 11p15) have been mapped to autosomes and one gene (SOS1) has been associated with the HGF trait observed to segregate in a dominant inheritance pattern. Here we report 11 individuals with HGF from three unrelated families. Whole-exome sequencing (WES) revealed three different truncating mutations including two frameshifts and one nonsense variant in RE1-silencing transcription factor (REST) in the probands from all families and further genetic and genomic analyses confirmed the WES-identified findings. REST is a transcriptional repressor that is expressed throughout the body; it has different roles in different cellular contexts, such as oncogenic and tumor-suppressor functions and hematopoietic and cardiac differentiation. Here we show the consequences of germline final-exon-truncating mutations in REST for organismal development and the association with the HGF phenotype.
Keywords: Adolescent; Base Sequence; Chromosome Segregation; Exons; Family; Female; Fibromatosis, Gingival; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Pedigree; Repressor Proteins

De novo missense variants in PPP1CB are associated with intellectual disability and congenital heart disease. - Ma, Lijiang; Bayram, Yavuz; McLaughlin, Heather M; Cho, Megan T; Krokosky, Alyson; Turner, Clesson E; Lindstrom, Kristin; Bupp, Caleb P; Mayberry, Katey; Mu, Weiyi; Bodurtha, Joann; Weinstein, Veronique; et al. (Hum Genet, 2016)
Intellectual disabilities are genetically heterogeneous and can be associated with congenital anomalies. Using whole-exome sequencing (WES), we identified five different de novo missense variants in the protein phosphatase-1 catalytic subunit beta (PPP1CB) gene in eight unrelated individuals who share an overlapping phenotype of dysmorphic features, macrocephaly, developmental delay or intellectual disability (ID), congenital heart disease, short stature, and skeletal and connective tissue abnormalities. Protein phosphatase-1 (PP1) is a serine/threonine-specific protein phosphatase involved in the dephosphorylation of a variety of proteins. The PPP1CB gene encodes a PP1 subunit that regulates the level of protein phosphorylation. All five altered amino acids we observed are highly conserved among the PP1 subunit family, and all are predicted to disrupt PP1 subunit binding and impair dephosphorylation. Our data suggest that our heterozygous de novo PPP1CB pathogenic variants are associated with syndromic intellectual disability.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Intellectual Disability; Male; Mutation, Missense; Phosphorylation; Protein Phosphatase 1

DVL3 Alleles Resulting in a -1 Frameshift of the Last Exon Mediate Autosomal-Dominant Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Hoischen, Alexander; Bayram, Yavuz; Withers, Marjorie; Gezdirici, Alper; Kimonis, Virginia; Steehouwer, Marloes; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; van Bon, Bregje W M; et al. (Am J Hum Genet, 2016)
Robinow syndrome is a rare congenital disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features. Recent reports have identified, in individuals with dominant Robinow syndrome, a specific type of variant characterized by being uniformly located in the penultimate exon of DVL1 and resulting in a -1 frameshift allele with a premature termination codon that escapes nonsense-mediated decay. Here, we studied a cohort of individuals who had been clinically diagnosed with Robinow syndrome but who had not received a molecular diagnosis from variant studies of DVL1, WNT5A, and ROR2. Because of the uniform location of frameshift variants in DVL1-mediated Robinow syndrome and the functional redundancy of DVL1, DVL2, and DVL3, we elected to pursue direct Sanger sequencing of the penultimate exon of DVL1 and its paralogs DVL2 and DVL3 to search for potential disease-associated variants. Remarkably, targeted sequencing identified five unrelated individuals harboring heterozygous, de novo frameshift variants in DVL3, including two splice acceptor mutations and three 1 bp deletions. Similar to the variants observed in DVL1-mediated Robinow syndrome, all variants in DVL3 result in a -1 frameshift, indicating that these highly specific alterations might be a common cause of dominant Robinow syndrome. Here, we review the current knowledge of these peculiar variant alleles in DVL1- and DVL3-mediated Robinow syndrome and further elucidate the phenotypic features present in subjects with DVL1 and DVL3 frameshift mutations.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Base Sequence; Codon, Nonsense; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exons; Female; Frameshift Mutation; Genetic Variation; Humans; Limb Deformities, Congenital; Male; Molecular Sequence Data; Phosphoproteins; Proto-Oncogene Proteins; Receptor Tyrosine Kinase-like Orphan Receptors; Sequence Analysis, DNA; Sequence Deletion; Urogenital Abnormalities; Wnt Proteins; Wnt-5a Protein

Identification of a RAI1-associated disease network through integration of exome sequencing, transcriptomics, and 3D genomics. - Loviglio, Maria Nicla; Beck, Christine R; White, Janson J; Leleu, Marion; Harel, Tamar; Guex, Nicolas; Niknejad, Anne; Bi, Weimin; Chen, Edward S; Crespo, Isaac; Yan, Jiong; Charng, Wu-Lin; et al. (Genome Med, 2016)
BACKGROUND: Smith-Magenis syndrome (SMS) is a developmental disability/multiple congenital anomaly disorder resulting from haploinsufficiency of RAI1. It is characterized by distinctive facial features, brachydactyly, sleep disturbances, and stereotypic behaviors. METHODS: We investigated a cohort of 15 individuals with a clinical suspicion of SMS who showed neither deletion in the SMS critical region nor damaging variants in RAI1 using whole exome sequencing. A combination of network analysis (co-expression and biomedical text mining), transcriptomics, and circularized chromatin conformation capture (4C-seq) was applied to verify whether modified genes are part of the same disease network as known SMS-causing genes. RESULTS: Potentially deleterious variants were identified in nine of these individuals using whole-exome sequencing. Eight of these changes affect KMT2D, ZEB2, MAP2K2, GLDC, CASK, MECP2, KDM5C, and POGZ, known to be associated with Kabuki syndrome 1, Mowat-Wilson syndrome, cardiofaciocutaneous syndrome, glycine encephalopathy, mental retardation and microcephaly with pontine and cerebellar hypoplasia, X-linked mental retardation 13, X-linked mental retardation Claes-Jensen type, and White-Sutton syndrome, respectively. The ninth individual carries a de novo variant in JAKMIP1, a regulator of neuronal translation that was recently found deleted in a patient with autism spectrum disorder. Analyses of co-expression and biomedical text mining suggest that these pathologies and SMS are part of the same disease network. Further support for this hypothesis was obtained from transcriptome profiling that showed that the expression levels of both Zeb2 and Map2k2 are perturbed in Rai1 mice. As an orthogonal approach to potentially contributory disease gene variants, we used chromatin conformation capture to reveal chromatin contacts between RAI1 and the loci flanking ZEB2 and GLDC, as well as between RAI1 and human orthologs of the genes that show perturbed expression in our Rai1 mouse model. CONCLUSIONS: These holistic studies of RAI1 and its interactions allow insights into SMS and other disorders associated with intellectual disability and behavioral abnormalities. Our findings support a pan-genomic approach to the molecular diagnosis of a distinctive disorder.
Keywords: Animals; Embryo, Mammalian; Exome; Female; Gene Regulatory Networks; Genomics; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors; Transcriptome